Influence of malaria transmission intensity and the 581G mutation on the efficacy of intermittent preventive treatment in pregnancy: systematic review and meta‐analysis. Issue 12 (30th September 2015) - Chico, R. Matthew; Cano, Jorge; Ariti, Cono; Collier, Timothy J.; Chandramohan, Daniel; Roper, Cally; Greenwood, Brian
Abstract: Objectives: To estimate where intermittent preventive treatment (IPTp) using sulphadoxine–pyrimethamine (SP) could be withdrawn as an intervention due to declining malaria transmission intensity, or due to increasing prevalence of the Plasmodium falciparum dihydropteroate synthetase resistance mutation at codon 581G. Methods: We conducted a systematic review and meta‐analysis of protection against the incidence of low birth weight (LBW) conferred by ≥2 doses of IPTp‐SP. We matched these outcomes to a proxy measure of malaria incidence in women of the same studies, applied meta‐regression models to these data and conducted sensitivity analysis of the 581G mutation. Results: Variation in the protective effect of IPTp‐SP against LBW could not be explained by malaria transmission intensity. Among primi‐ and secundigravidae, IPTp‐SP protected against LBW where 581G was ≤10.1% [odds ratio (OR): 0.49; 95% confidence intervals (CI): 0.29, 0.81; P = <0.01] and 581G was >10.1% (OR = 0.73; 95% CI: 0.29, 1.81; P = 0.03). Random‐effects models among multigravidae showed that IPTp‐SP protects against LBW where 581G was ≤10.1% (OR = 0.56; 95% CI: 0.37, 0.86; P = 0.07), a finding of borderline statistical significance. No evidence of protection against LBW was observed where 581G was >10.1% (OR = 0.96; 95% CI: 0.70, 1.34; P = 0.47). Conclusion: There appears to be a prevalence of 581G above which IPTp‐SP no longer protects against LBW. Pregnancy studies are urgently needed where 581G is >10.1% to define the specific prevalence threshold where new strategies should be deployed.